Nutritional Applications of Green Magnesium Nanoparticles as Functional Feed Additives in Broiler Diets: Towards Sustainable Poultry Production - Fayiz M. Reda; Ayman S. Salah; Ayman E. Taha; Frank Idan; Zhongxin Zhou; Samar S. Bassiony; Laila A. Mohamed; Mahmoud Alagawany (Veterinary Medicine and Science, 2026)
ABSTRACT Background Nanoparticles, including green magnesium nanoparticles, facilitate passage through cellular membranes in animals and interact efficiently with biological systems, improving their functional activity. Consequently, the utilization of green magnesium nanoparticles is recommended to enhance the availability of magnesium, thus boosting its metabolism and uptake. Objectives The current research aimed to examine the impacts of biological magnesium nanoparticles (BNMg) as a feed additive on growth efficiency, haematological parameters, biochemical parameters, antioxidant efficacy, immune system activities, blood minerals, digestive enzymes, carcass traits and caecal microbiota in broiler chickens. Methods A total of 250 unsexed Ross 1‐day‐old broiler chicks were randomly allocated into five groups, each containing 50 birds. Five replicates of each group were established, with each replicate comprising 10 birds. The control group was fed a diet devoid of BNMg, but the rest of the groups were provided diets enriched with BNMg at levels of 150, 300, 450 and 600 mg/kg, respectively. Results The outcomes demonstrated a substantial improvement in all performance parameters. BNMg administration significantly elevated carcass and dressing, and decreased abdominal fat percentage compared to control. BNMg supplementation markedly decreased glucose levels and elevated haemoglobin and red and white blood cells. BNMg administration elevated blood total protein and globulin, while concurrently decreasing aspartate aminotransferase and alanine. The inclusion of BNMg in broiler diets increased blood magnesium levels and noticeably enhanced lipid profile, immunity markers, antioxidant activities and digestive enzymes. Moreover, BNMg supplementation increased the concentration of copper, potassium and zinc in the blood. BNMg markedly elevated the population of lactic acid bacteria while dramatically reducing the overall counts of total bacteria, coliforms, Escherichia coli , Salmonella , total yeast and mould counts. Conclusion BNMg supplementation enhances growth performance, haematological parameters, blood chemistry, antioxidant efficacy, immune system status, blood minerals, digestive enzymes and caecal microbiota without any adverse effects on broiler health.